Strategic Business Taxation when Finance and Portfolio Decisions are Endogenous - Andreas Wagener (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 1997)
The paper analyzes the impact of personal income taxes on strategic business taxation. It sets up a model of tax competition between small jurisdictions whose governments are revenue maximizers and use business taxes on the capital stock and on corporate profits as their policy instruments. Personal income taxes, which are parametrically fixed, discriminate between dividends and interest incomes and determine portfolio choices of households and finance decisions of firms. It turns out that the strategic incentives in business taxation are strongly influenced by personal income tax parameters. In the case of profit taxation this influence is non- monotonic and discontinuous. Generally, Leviathan governments prefer fully equity financed firms. It can be shown that from a government viewpoint profit and capital taxes are perfect substitutes as they create identical strategic incentives.
Keywords: H25; H71; H77; 330